Process Optimisation of Ultrasound-Assisted Extraction of Oligosaccharides from Coconut Husk - Shie-Lih Tang; Siew-Ling Hii; Chen-Chung Koh (The Scientific World Journal, 2023)
A fractional factorial design was used to investigate the ultrasound-assisted extraction (UAE) of oligosaccharides from coconut husk, an agroindustry by-product. The effects of five key influencing parameters (X1, incubation temperature; X2, extraction duration; X3, ultrasonicator power; X4, NaOH concentration; X5, solid-to-liquid ratio) were studied. Total carbohydrate content (TC), total reducing sugar (TRS), and degree of polymerisation (DP) were the dependent variables. The optimal extraction condition was attained when oligosaccharides with a desired DP of 3.72 were extracted when the coconut husk in a liquid-to-solid ratio of 127 mL/g was treated with 1.05 percent (w/v) of NaOH solution at an incubation temperature of 30.4°C for 5 min using an ultrasonicator power of 248 W. The optimised parameters for oligosaccharide extraction from coconut husk reported in this study could be useful for the effective isolation of these compounds for prebiotic research.